Verbal Communication at Workplace: A Pragmatic Approach - et. al., Dr. Sunil Kumar Jha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The academicians and the professionals classify communication into two broader categories; verbal and non-verbal. These two labels of distinction might have earned popularity on the basis of easier way of understanding things but the gravity of the subject calls for a fresh and new approach which is felt quite essential to have in-depth and holistic study of the issue. The verbal is said to have direct and rational relationship with communication through words whereas the other forms of messages have been categorized as non-verbal. The paper explores some of the unexplored aspects of verbal mode of communication that encompasses within its purview the pragmatic approach to linguistic discourse in the total system of communication. Further, the paper also endeavors to point out some of the aspects of communication that relates to the principles of management of an organization which need be considered in the matter of TQM (Total Quality Management).